MEMBANGUN SISTEM INFORMASI AKADEMIK PESANTREN DI KABUPATEN MALANG (PEMBINAAN PROGRAM DIGITALISASI DAN OTOMASI DI PESANTREN CENTER) - Abdurrahman (Institute Agama Islam Al-Qolam Malang, 2023)
After the state's recognition of pesantren through undang-undang as an institution with three functions at once; education, da’wah and community empowerment, then it was followed by several regulations under it. Some of these regulations mandate pesantren to be officially registered with the relevant Ministry. however - from the existing data - there are still many pesantren that have not fulfilled or have not even continued their operational permits (IJOP), also to updating EMIS data at the Ministry of Religion. This research is intended to form and develop the digitization of the pesantren academic information system (SIAP) in accordance with the technical instructions on applying for operational permits (IJOP) and reporting of Emis data from the Ministry of Religion, as well as making the aggregation data in the system a directory data at the Pesantren Center Nusantara. For this purpose, this study uses the research and development (R&D) method through an asset-based community development (ABCD) approach which includes physical capital, human capital and social capital. The research process includes planning the implementation, which includes stakeholder agreements to carry out prior training socialization to pesantren. The socialization was attended by 51 pesantren which then formed a coordinating group through social media with 100 pesantren as members. After the socialization was successfully carried out, it was followed by direct training related to two important themes; IJOP and Emis data reporting. From the results of the training, a team was formed to develop the pesantren academic information system (SIAP) App, which was agreed to include three features at once; starting with IJOP feature, the Emis data reporting feature and SIAP feature. This research was quite successful in garnering the participation of all important stakeholders consisting of the Pesantren Center Nusantara, PC RMI NU Kabupaten Malang and PD Pontren Kemenag, which then agreed to develop a system of assistance to pesantren in Kabupaten Malang related to IJOP, Emis and SIAP submissions. This research also succeeded in creating a team for the development of SIAP application by loading three features at once.